Effects of Salinity and Inundation on Microbial Community Structure and Function in a Mangrove Peat Soil - Chambers, Lisa G.; Guevara, Rafael; Boyer, Joseph N.; Troxler, Tiffany G.; Davis, Stephen E. (Wetlands (Wilmington, N.C.), 2016)
Shifts in microbial community function and structure can be indicators of environmental stress and ecosystem change in wetland soils. This study evaluated the effects of increased salinity, increased inundation, and their combination, on soil microbial function (enzyme activity) and structure (phospholipid fatty acid (PLFA) signatures and terminal restriction fragment length polymorphisms (T-RFLP) profiles) in a brackish mangrove peat soil using tidal mesocosms (Everglades, Florida, USA). Increased tidal inundation resulted in reduced soil enzyme activity, especially alkaline phosphatase, an increase in the abundance and diversity of prokaryotes, and a decline in number of eukaryotes. The community composition of less abundant bacteria (T-RFLPs comprising 0.3–1 % of total fluorescence) also shifted as a result of increased inundation under ambient salinity. Several key biogeochemical indicators (oxidation-reduction potential, CO 2 flux, porewater NH 4 + , and dissolved organic carbon) correlated with measured microbial parameters and differed with inundation level. This study indicates microbial function and composition in brackish soil is more strongly impacted by increased inundation than increased salinity. The observed divergence of microbial indicators within a short time span (10-weeks) demonstrates their usefulness as an early warning signal for shifts in coastal wetland ecosystems due to sea level rise stressors.